2016
DOI: 10.3390/ijms17060851
|View full text |Cite
|
Sign up to set email alerts
|

Host Plants Identification for Adult Agrotis ipsilon, a Long-Distance Migratory Insect

Abstract: In this study, we determined the host relationship of Agrotis ipsilon moths by identifying pollen species adhering them during their long-distance migration. Pollen carried by A. ipsilon moths was collected from 2012 to 2014 on a small island in the center of the Bohai Strait, which is a seasonal migration pathway of this pest species. Genomic DNA of single pollen grains was amplified by using whole genome amplification technology, and a portion of the chloroplast rbcL sequence was then amplified from this mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 35 publications
12
48
0
Order By: Relevance
“…Pollen of closely related plants may have highly similar morphology, and thus should be distinguished using DNAbased techniques (Liu et al 2016), or by differences in geographical distribution and flowering periods (Xu et al 1999). In our study, if the pollen attached to M. separata moth could only be identified to the genus level, then all species in this genus in China were treated as potential candidate nectar plants.…”
Section: Analysis Of Distribution and Flowering Periods Of Candidate mentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen of closely related plants may have highly similar morphology, and thus should be distinguished using DNAbased techniques (Liu et al 2016), or by differences in geographical distribution and flowering periods (Xu et al 1999). In our study, if the pollen attached to M. separata moth could only be identified to the genus level, then all species in this genus in China were treated as potential candidate nectar plants.…”
Section: Analysis Of Distribution and Flowering Periods Of Candidate mentioning
confidence: 99%
“…Xu et al (1999) examined pollen attached to 101 moths of cotton bollworm, Helicoverpa armigera, by scanning electron microscopy, and proposed that the host of H. armigera moth could be divided into two types: feeding hosts and oviposition hosts. By a combination of DNA barcoding and pollen morphology, Liu et al (2016) found 28 species of pollen from 18 plant families on the tested moths of A. ipsilon. However, few papers have provided supporting evidence for the importance of nectar plants in pest epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…The black cutworm, Agrotis ipsilon (Lepidoptera: Nocutuidae), is an underground destructive pest that is difficult to prevent and control. It feeds on nearly all varieties of vegetables and many important grains (Liu et al, 2016). It has long-distance migration behavior which can cause widespread harm.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Agrotis ipsilon caterpillars performed relatively well on both species, and in contrast, suffered almost 100 % mortality on the control diet of store-bought leaf lettuce. Because A. ipsilon is a common agricultural pest (Liu et al 2016), we expected high performance on the lettuce diet. To reduce the likelihood that lettuce would include pesticides or other chemicals that would affect caterpillar development, we purchased organic lettuce and washed it thoroughly before offering it to caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…For the whole-leaf bioassay, the black cutworm, Agrotis ipsilon was used; for the chemical extract bioassay, Chrysodeixis eriosoma was used. Agrotis ipsilon is a widespread agricultural pest found worldwide, including on many islands, which feeds on a diversity of agricultural crops from at least 18 plant families (Liu et al 2016). A. ipsilon caterpillars used in this study were reared from eggs laid on paper towels from moths captured from the vicinity of agricultural fields in Hilo, Hawaii Island in September 2015.…”
Section: Methodsmentioning
confidence: 99%